设 $a_n > 0$ 且 $\lim _{n \rightarrow \infty}\left(a_1+a_2+\cdots+a_n\right)$ 收玫,数列 $\left\{y_n\right\}: y_1=1,2 y_{n+1}=y_n+\sqrt{y_n^2+a_n}(n=1,2, \cdots)$. 证明: $\left\{y_n\right\}$ 是单调增加的且收敛的数列.
【答案】 有题设知 $y_n > 0$,改写数列$\{y_n\}$ 得
$$
\mathbf{2} y_{n+1}-\mathbf{2} y_n=\sqrt{y_n^2+a_n}-y_n > 0
$$
即 $y_{n+1} \geq y_n$ ,所以数列 $\left\{y_n\right\}$ 是单调增加.
用归纳法证明 $y_n > 1$. 因为 $y_1=1$, 得
$$
2 y_2=y_1+\sqrt{y_1^2+a_1}=1+\sqrt{1+a_1} > 2
$$
即 $y_2 > 1$. 从而
$$
2 y_n=y_{n-1}+\sqrt{y_{n-1}^2+a_{n-1}} \geq 1+\sqrt{1+a_{n-1}} > 2
$$
所以 $y_n > 1$. 从而得
$$
\sqrt{y_n^2+a_n}+y_n > \sqrt{1+a_n}+1 > 2
$$
另外,由于
$$
y_{n+1}-y_n=\frac{a_n}{2\left(\sqrt{y_n^2+a_n}+y_n\right)} < \frac{a_n}{4}
$$
设 $\lim _{n \rightarrow \infty}\left(a_1+a_2+\cdots+a_n\right)=c$ ,从而可得
$$
y_{n+1}-y_1=\sum_{k=1}^n\left(y_{k+1}-y_k\right) < \frac{1}{4} \sum_{k=1}^n a_n < \frac{c}{4}
$$
所以 $y_n < \frac{c}{4}+y_1$. 即 $\left\{y_n\right\}$ 是单调增加的且收敛的收敛.


系统推荐